Tilmanocept as a novel tracer for lymphatic mapping and sentinel lymph node biopsy in melanoma and oral cancer. Issue 10 (18th July 2022) - Mwagiru, Derek; Shivashankar, Pranav; Wong, Eva; Farlow, David; Cambden, Brad; Abdul‐Razak, Muzib
Abstract: Background: Sentinel lymph node biopsy (SLNB) has been pivotal for pathological assessment of nodal status in cutaneous melanoma (CM) and oral cavity squamous cell carcinoma (OCSCC) thus crucial for staging. An ideal agent for lymphatic mapping should have a standardized preparation, appropriate accumulation in first‐echelon nodes and no side effects. Tilmanocept, a CD206‐receptor targeted novel radiotracer fulfils these properties. This study investigated Tilmanocept for lymphoscintigraphy and intraoperative identification of sentinel lymph nodes (SLN) in CM and OCSCC. Methods: This prospective cross sectional study examined patients who presented to Crown Princess Mary Cancer Centre, Westmead Hospital, Sydney. Patients had biopsy proven tumours with clinically and radiologically negative regional lymph nodes. Tilmanocept guided lymphoscintigraphy was followed by intraoperative SLNs identification via handheld gamma probe. Primary endpoints were detection and retrieval rate of SLNs while secondary endpoints included pathological status of SLNs. Results: Thirty‐five patients were included (26 with CM and 9 with OCSCC) with the most common primary tumour site for CM on the extremities (33.3%). Lymphoscintigraphy with Tilmanocept identified at least 1 SLN (sensitivity 100%) in all patients. SLNs were retrieved in all of patients intraoperatively (100% retrieval rate) with positive nodes found in 20% of patients. Tilmanocept also demonstrated 100% tissue specificity, with lymph nodal tissue confirmed histologically, with no false positives. Conclusion: Tilmanocept is a reliable radiotracer for assessing the nodal status in patients with CM and OCSCC. Our group is the first to evaluate the use of Tilmanocept in the Australian setting, adding to the limited studies worldwide. Abstract : Our study is evaluation of novel radioactive tracer Tilmanocept in performing sentinel node biopsy in cutaneous melanoma and oral cancer. Tilmanocept identified at least one sentinel node in all patients and this was retrieved leading to a 100% sensitivity in the technique.Tilmanocept is a reliable radio tracer for assessing the nodal status in these patients.